Assessing the Impact of Cultural Integration on the Indonesian Legal System from Multicultural Perspective - Andika Ronggo Gumuruh; Moh. Farhan (Rechtenstudent, 2025)
Legal analysis in the context of multiculturalism in Indonesia is essential to understand how cultural diversity influences and shapes the national legal system. Indonesia’s rich plurality of ethnicities, traditions, and belief systems presents both opportunities and challenges in harmonizing state law with local values. The development of legal pluralism demonstrates that Indonesian law is not solely built upon positive law, but is also influenced by social norms and cultural practices embedded within society. This condition highlights the importance of examining how law can function as a tool of integration in a multicultural environment while simultaneously ensuring the protection of individual rights. One of the key challenges in legal compliance arises from deeply rooted cultural patterns, particularly patriarchal norms that continue to affect legal interpretation and implementation. Using a library research method combined with normative legal analysis, this study draws upon statutory regulations, official legal documents, and academic literature to explore the relationship between multiculturalism and the legal system. The study concludes that, first, cultural integration significantly affects the Indonesian legal system, contributing both positive developments and complex challenges. Second, the main difficulty lies in balancing cultural autonomy with adherence to universal national legal principles. Third, the Indonesian legal system has progressively adapted to accommodate multicultural realities, although continuous refinement remains necessary.